AN AUTOMATED FLOW MODEL (FOR SIGNING DOCUMENTS IN SEI) USING POWER AUTOMATE AND SHAREPOINT:: a case estudy - Oliveira Ferreira, Vivian Anne; Clarismundo Borges, Daniel (Revista Interface Tecnológica, 2022)
In contemporary times, the need for automation to streamline bureaucratic processes within the public administration is frequent and we have many tools, including free ones, available in the virtual environment. With the proposal to facilitate them, Microsoft's Power Platform can generate customized flows with its applications, so that even the most lay people on the subject can structure them, and keep fixed models of these creations for frequent use. The purpose of this article is to demonstrate a flow developed for the document signature request in the billing area, integrated to the SEI! portal (Electronic Information System) and created by two tools: Power Automate and Sharepoint, which combined promote its operation. The first one formats the flow and the second one triggers it. Finally, Outlook and Teams receive these notifications and promote actions for the progress and closure of this task cycle. It has already been tested and presented good results in an administrative routine in the public sphere.
Keywords: workflow management; process management; power automate; sharepoint; agile methodology